2022
DOI: 10.2147/jmdh.s380171
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with COVID-19 Vaccination Acceptance Among Muslim High School Students in Jakarta Metropolitan Area, Indonesia

Abstract: Purpose This study aims to identify the factors associated with COVID-19 vaccination uptake and the intention to receive the COVID-19 vaccine among Muslim high school students in Jakarta, Indonesia. Patients and Methods A cross-sectional study using an online survey was conducted for high school students. The population in this study were Muslim students grade 11 and 12 at secondary high school living and studying in Jakarta Metropolitan area. A total of 440 samples hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Moreover, several studies have shown that the HBM constructs can serve as an important predictor of influenza vaccination uptake (Brewer et al, 2007; Shahrabani, Benzion & Yom Din, 2009; Shahrabani & Benzion, 2010; Tsutsui, Benzion & Shahrabani, 2012; Alsuwailem et al, 2023). During the COVID-19 pandemic, the HBM was used to assess the root causes of COVID-19 vaccine hesitancy in the Asia-Pacific region and beyond (Kabir et al, 2021; Alobaidi, 2021; Huynh et al, 2021; Zilhadia et al, 2022; Jian Ng et al, 2022; Shah et al, 2022; Seangpraw et al, 2022b,a; Limbu, Gautam & Pham, 2022b; Ghazy et al, 2022; Hidayana et al, 2022; Qin et al, 2022; Harutyunyan et al, 2023; Berger et al, 2023; Toledo-López et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, several studies have shown that the HBM constructs can serve as an important predictor of influenza vaccination uptake (Brewer et al, 2007; Shahrabani, Benzion & Yom Din, 2009; Shahrabani & Benzion, 2010; Tsutsui, Benzion & Shahrabani, 2012; Alsuwailem et al, 2023). During the COVID-19 pandemic, the HBM was used to assess the root causes of COVID-19 vaccine hesitancy in the Asia-Pacific region and beyond (Kabir et al, 2021; Alobaidi, 2021; Huynh et al, 2021; Zilhadia et al, 2022; Jian Ng et al, 2022; Shah et al, 2022; Seangpraw et al, 2022b,a; Limbu, Gautam & Pham, 2022b; Ghazy et al, 2022; Hidayana et al, 2022; Qin et al, 2022; Harutyunyan et al, 2023; Berger et al, 2023; Toledo-López et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…During the COVID-19 pandemic, the HBM was used to assess the root causes of COVID-19 vaccine hesitancy in the Asia-Pacific region and beyond (Kabir et al, 2021;Alobaidi, 2021;Huynh et al, 2021;Zilhadia et al, 2022;Jian Ng et al, 2022;Shah et al, 2022;Seangpraw et al, 2022b, Ghazy et al, 2022;Hidayana et al, 2022;Qin et al, 2022;Harutyunyan et al, 2023;Berger et al, 2023;Toledo-López et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Perspective and acceptance studies are significant because they offer vital information that health education programs can use to target particular groups and increase vaccination rates (Fadloli Mubarok et al, 2021;Maulana et al, 2021;Trepanowski & Drążkowski, 2022). The differences in perspective and acceptance regarding the COVID-19 vaccination program have occurred in various countries (Alqudeimat et al, 2021;Raja et al, 2022;Munaa et al, 2021;Sharun et al, 2020;Zilhadia et al, 2022). In India, of the 351 participants, 86.3% planned to receive the COVID-19 vaccination, while 13.7% confessed to having second thoughts (Sharun et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Concern about safety and halal aspects was the reason respondents rejected the program (UNICEF Indonesia, 2020), and this resistance was quite common among Islamic boarding schools (Zilhadia et al, 2022). At the Islamic boarding school, the COVID-19 immunization was mostly rejected.…”
Section: Introductionmentioning
confidence: 99%